Does Fiscal Policy Affect Interest Rates? : Evidence from a Factor-Augmented Panel - Dell'Erba, Salvatore (IMF Working Papers; Working Paper ;, 2013)
This paper reconsiders the effects of fiscal policy on long-term interest rates employing a Factor Augmented Panel (FAP) to control for the presence of common unobservable factors. We construct a real-time dataset of macroeconomic and fiscal variables for a panel of OECD countries for the period 1989-2012. We find that two global factors-the global monetary and fiscal policy stances-explain more than 60 percent of the variance in the long-term interest rates. Compared to the estimates from models which do not account for global factors, we find that the importance of domestic variables in explaining long-term interest rates is weakened. Moreover, the propagation of global fiscal shocks is larger in economies characterized by macroeconomic and institutional weaknesses.